Opening Ceremony of Equador Photo Exhibition - Anon (Universiti Malaysia Perlis (UniMAP), 2013)
Opening Ceremony of Equador Photo Exhibition "Sons of the Sacret Waterfalls" and Perlis Art exhibition "Inspirasi Alam 2012" organized by Universiti Malaysia Perlis, Perpustakaan Negara Malaysia Negeri Perlis, Yayasan Tuanku Syed Putra, Embassy of Equador, Malaysia, 4th July 2012 and was held at Perlis State Public Library then after that the exhibition was held at The Library, Universiti Malaysia Perlis, Pauh Putra Campus, Perlis, Malaysia.